Impact of Facility Volume on Patient Safety Indicator Events After Transsphenoidal Pituitary Surgery. (26th January 2023) - Lemdani, Mehdi S.; Choudhry, Hannaan S.; Tseng, Christopher C.; Fang, Christina H.; Sukyte‐Raube, Donata; Patel, Prayag; Eloy, Jean Anderson
Abstract: Objectives: To investigate the impact of facility volume on Patient Safety Indicator (PSI) events following transsphenoidal pituitary surgery (TSPS). Study Design: Retrospective database review. Setting: National Inpatient Sample database (2003‐2011). Methods: The National Inpatient Sample was queried for TSPS cases from 2003 to 2011. Facility volume was defined by tertile of average annual number of TSPS procedures performed. PSIs, based on in‐hospital complications identified by the Agency of Healthcare Research and Quality, and poor outcomes, such as mortality and tracheostomy, were analyzed. Results: An overall 16, 039 cases were included: 804 had ≥1 PSI and 15, 235 had none. A greater proportion of male to female (5.8% vs 4.3%) and Black to White (7.0% vs 4.5%) patients experienced PSIs. There was an increased likelihood of poor outcome (odds ratio [OR], 3.1 [95% CI, 2.5‐3.7]; P < .001) and mortality (OR, 30.1 [95% CI, 18.5‐48.8]; P < .001) with a PSI. The incidence rates of PSIs at low‐, intermediate‐, and high‐volume facilities were 5.7%, 5.1%, and 4.2%, respectively. Odds of poor outcome with PSIs were greater at low‐volume facilities (OR, 3.3 [95% CI, 2.4‐4.4]; P < .001) vs intermediate (OR, 3.1 [95% CI, 2.1‐4.2]; P < .001) and high (OR, 2.5 [95% CI, 1.7‐3.8]; P < .001). Odds of mortality with PSIs were greater at high‐volume facilities (OR, 43.0 [95% CI, 14.3‐129.4]; P < .001) vs intermediate (OR, 40.0 [95% CI, 18.5‐86.4]; P < .001) and low (OR, 17.3 [95% CI, 8.0‐37.7]; P < .001). Conclusion: PSIs were associated with a higher likelihood of poor outcome and mortality following TSPS. Patients who experienced PSIs had a lower risk of poor outcome but increased mortality at higher‐volume facilities.